New particle formation in Beijing, China: Statistical analysis of a 1-year data set - ZJ Wu; Hu, M.; S. Liu; Wehner, B.; Bauer, S.; Ssling, A. M.; Wiedensohler, A.; Petaja, T.; Dal Maso, M.; Kulmala, M. (Journal of Geophysical Research-Atmospheres, 2007)
Particle number size distributions between 3 nm and 10 mm were measured in Beijing, China. New particle formation events were observed on around 40% of the measurement days from March 2004 to February 2005 and were generally observed under low relative humidity and sunny conditions. Though occurring during all seasons, new particle formation events had highest frequency in spring and lowest frequency in summer. Events were classified as "clean'' or "polluted'' groups mainly according to the condensational sink and the local wind. The formation rate range was from 3.3 to 81.4 cm(-3) s(-1). The growth rate varied from 0.1 to 11.2 nm h(-1). The seasonal variation of condensable vapor concentration showed the highest values during summer months due to enhanced photochemical and biological activities as well as stagnant air masses preventing exchange with cleaner air.
Keywords: aerosol-size distributions; atmospheric particles; boreal forest; boundary-layer; gas-phase; growth; Meteorology & Atmospheric Sciences; mode particles; nucleation events; parameters; rates